Bonifacio ang unang pangulo - Padilla, Robin; Morales, Vina; Padilla, Daniel
"The true story of Andres Bonifacio, a man who rose as a leader in the fight against the Spanish oppressors, and would gain the enmity of even those fighting for the same cause."